Smartphone-integrated urinary CTX-II immunosensor based on wavelength filtering from chromogenic reaction - Kim, Saemi; Chun, Hyeong Jin; Lee, Kyung Won; Yoon, Hyun C. (Biosensors and Bioelectronics, 2020)
The integration of smart IT devices and biochemical assays with optical biosensing technology facilitates the development of efficacious optical biosensors for many practical diagnostic fields, owing to their minimized use of high-technical electronic components and simple operation. Herein, we introduced a simple optical biosensing system based on the specific wavelength filtering principle and count-based analysis method. The developed system uses a smartphone with a paper-based signal guide and a biosensing channel. The paper-based signal guide was prepared by printing red patterns of various brightness on a black background. Given that a blue product is generated as a result of horseradish peroxidase (HRP)-based enzymatic reaction in the biosensing channel, the channel could be used as a blue filter that absorbs red light. When red light reflected from the red pattern is absorbed by the channel, the pattern appears black. As such, the color of the patterns is assimilated with the black background, so it seems to disappear. Consequently, the amount of blue product relative to the concentration of the target analyte can be measured by counting the number of observed patterns on the paper-based signal guide. In this study, the concentration of urinary C-telopeptide fragment of type II collagen (uCTX-II, 0–10 ng/mL) was measured using the developed system without complicated equipment. In addition, the quantitative analysis of uCTX-II in the real urine sample was successfully performed. Therefore, we expect that the developed optical transducing system could be practically used for point-of-care testing (POCT) diagnosis under resource-limited environmental conditions.
Keywords: Artificial urines; Chromogenic reaction; Count-based analysis; Environmental conditions; Filtering effects; Horseradish peroxidase; Point-of-care testing; Wavelength filtering; Biosensing Techniques; Collagen Type II; Colorimetry; Equipment Design; Humans; Limit of Detection; Paper; Peptide Fragments; Point-of-Care Testing; Smartphone; Artificial urine; Count-based analysis; Filtering effect; Point-of-care testing (POCT); Smartphone-based biosensor; uCTX-II detection